Applying Chinese culture heritage elements to glass product design / Qingfeng Liu and Nurul 'Ayn Ahmad Sayuti - Liu, Qingfeng; Ahmad Sayuti, Nurul 'Ayn (College of Creative Arts, 2024)
Developing products with added cultural value has become one of the main means of promoting economic growth in China, which can enhance local cultural influence and improve the quality of people's spiritual lives. What’s more, with the development of China's economy, people are more inclined to a high quality of life and a culture that caters to their spiritual needs. On the other hand, glass has become a standard industrial material and is increasingly widely used. Daily glass products occupy a significant share of life. However, the connection with traditional Chinese culture has been lost in the design of glass products, and there is a separation between China's economic transformation and the revitalization of cultural industries. This study aims to find ways to successfully integrate Chinese cultural heritage elements into glass product design. In the case study session, this study analyses the main visual components level of cultural heritage based on many different views, mainly divided into three components: color, shape, and decoration. At the same time, it also puts forward the meaning level of cultural heritage and its transformation process. There are also amounts of glass products with cultural heritage elements as examples, which provide valuable references for researchers to analyze how to integrate cultural elements from the visual level and meaning level. The key factors that influence the success of glass product design are also described in this paper, which provides a basis for further research.